Preliminary Efficacy of Adapted Responsive Teaching for Infants at Risk of Autism Spectrum Disorder in a Community Sample. (11th January 2015) - Baranek, Grace T.; Watson, Linda R.; Turner-Brown, Lauren; Field, Samuel H.; Crais, Elizabeth R.; Wakeford, Linn; Little, Lauren M.; Reznick, J. Steven
Abstract : This study examined the (a) feasibility of enrolling 12-month-olds at risk of ASD from a community sample into a randomized controlled trial, (b) subsequent utilization of community services, and (c) potential of a novel parent-mediated intervention to improve outcomes. The First Year Inventory was used to screen and recruit 12-month-old infants at risk of ASD to compare the effects of 6–9 months of Adapted Responsive Teaching (ART) versus referral to early intervention and monitoring (REIM). Eighteen families were followed for 20 months. Assessments were conducted before randomization, after treatment, and at 6-month follow-up. Utilization of community services was highest for the REIM group. ART significantly outperformed REIM on parent-reported and observed measures of child receptive language with good linear model fit. Multiphase growth models had better fit for more variables, showing the greatest effects in the active treatment phase, where ART outperformed REIM on parental interactive style (less directive), child sensory responsiveness (less hyporesponsive), and adaptive behavior (increased communication and socialization). This study demonstrates the promise of a parent-mediated intervention for improving developmental outcomes for infants at risk of ASD in a community sample and highlights the utility of earlier identification for access to community services earlier than standard practice.